2006
DOI: 10.1158/0008-5472.can-05-2304
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Dependence of Breast Cancer Cells versus Normal Cells on Integrin-Linked Kinase for Protein Kinase B/Akt Activation and Cell Survival

Abstract: The emerging paradigm of ''oncogene addiction'' has been called an Achilles' heel of cancer that can be exploited therapeutically. Here, we show that integrin-linked kinase (ILK), which is either activated or overexpressed in many types of cancers, is a critical regulator of breast cancer cell survival through the protein kinase B (PKB)/Akt pathway but is largely dispensable for the survival of normal breast epithelial cells and mesenchymal cells. We show that inhibition of ILK activity with a pharmacologic IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 53 publications
(66 reference statements)
6
133
1
Order By: Relevance
“…Transient transfection of wild-type ILK (ILK-WT) increased Tcf/ Lef transcriptional activity over Wnt3a alone (Figure 2a), whereas transfection of ILK-DN reduced the Wnt3a-induced activation of this transcription factor in a dose-dependent manner (Figure 2a). ILK activity was also inhibited by treatment with a second generation of a highly selective small molecule ILK inhibitor, QLT-0267 (Zhou et al, 2004), which inhibits ILK kinase activity in a dose-dependent manner (Troussard et al, 2006). We have recently shown the specificity of this ILK inhibitor in another study by overexpressing a constitutively active mutant of ILK in the presence of QLT-0267, and showing that this active ILK rescued the effect of the inhibitor (Troussard et al,…”
Section: Resultsmentioning
confidence: 99%
“…Transient transfection of wild-type ILK (ILK-WT) increased Tcf/ Lef transcriptional activity over Wnt3a alone (Figure 2a), whereas transfection of ILK-DN reduced the Wnt3a-induced activation of this transcription factor in a dose-dependent manner (Figure 2a). ILK activity was also inhibited by treatment with a second generation of a highly selective small molecule ILK inhibitor, QLT-0267 (Zhou et al, 2004), which inhibits ILK kinase activity in a dose-dependent manner (Troussard et al, 2006). We have recently shown the specificity of this ILK inhibitor in another study by overexpressing a constitutively active mutant of ILK in the presence of QLT-0267, and showing that this active ILK rescued the effect of the inhibitor (Troussard et al,…”
Section: Resultsmentioning
confidence: 99%
“…One small molecule inhibitor that has been used to target ILK is QLT0267. This second-generation ILK inhibitor inhibits the kinase activity of ILK and it exhibits a high degree of selectivity against a wide panel of protein kinases (Troussard et al, 2006). Using this in vitro invasion assay, we showed incubation of the tumor cells with 10 mM QLT0267 impaired invasion into the collagen I gel (Figure 5e).…”
Section: Pharmacological Inhibition Of Ilk In Established Erbb2 Tumormentioning
confidence: 93%
“…Whereas ILK-induced AKT phosphorylation on its serine residue S473 increases cell survival by promoting anoikis resistance , phosphorylation of this residue also induces VEGF-dependent angiogenesis in cancer cell lines (Tan et al, 2004). Conversely, inhibition of ILK or ILK-PINCH function markedly decreases AKT phosphorylation in number of normal and cancer cell lines (Persad et al, 2000;Fukuda et al, 2003aFukuda et al, , 2003bHannigan et al, 2005;Koul et al, 2005;Younes et al, 2005;Troussard et al, 2006). Recent data have also shown that ILK functionally interacts with mTORC2 (Troussard et al, 2006), through a direct interaction with Rictor, a component of the mTOR complex 2 (McDonald et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…About 1.4% of breast cancers also contain a mutation in AKT1 (E17 K) that confers constitutive activity (Carpten et al, 2007;Stemke-Hale et al, 2008). Other regulators, 3-phosphoinositidedependent protein kinase 1 (PDK1) or integrin-linked kinase (ILK) activate AKT1 by inducing phosphorylation of S308 or S473 (Lawlor and Alessi, 2001;Troussard et al, 2006). The role of PDK1 or ILK in the mechanisms of resistance to trastuzumab is not known at present.…”
Section: Regulation Of Akt1mentioning
confidence: 99%